BOGOR RADAR MEDIA STRATEGY IN MAINTAINING ITS PRINT MEDIA IN THE DIGITAL ERA - Febria Adha Larasati; Ditha Dzakiyah Meiliani Putri; Reynaldi Agustin (Jurnal Komunikasi dan Kebudayaan, 2021)
The main problem raised in this research is the strategy of print media in the digital era (Radar Bogor). The formulation of the problem discussed in this study is how the Radar Bogor print media survives in the digital era. The purpose of this study was to determine the success of Radar Bogor in implementing its strategy. The research method used is a qualitative research method that describes the adaptation of print media to globalization in order to continue to exist in the digital era. The resource persons in this study were the media staff of Radar Bogor. Data was collected by means of interviews. The results of research on Radar Bogor show that (1) as a form of expression for Radar Bogor companies in responding to globalization, namely trying to maximize the use of technology by presenting their products on the website. Compared to print media, online media is more practical, and with sufficient internet quota, readers will find it easier to enjoy journalistic products from Radar Bogor. (2) a strategy for marketing and raising the media's profile by promoting it online as well as at thematic events tailored to national holidays.The media also strives to strengthen the quality of journalists and form a strong work team for internal marketing within the company. (3) To be more accountable for news products, the media is obliged to balance the news in each article. It is intended that the media have valid and quality data.